Rozrachunek z przeszłością (radzieckie i rosyjskie dyskusje wokół pojęcia stalinizmu) - Stobiecki, Rafał (Acta Universitatis Lodziensis. Folia Historica, 1995)
This article is an attempt of presenting and analysing the last soviet and russian discussions on stalinism. The policy of pierestroika and glasnost started by Michail Gorbaczov released the social need of an account with the past, especially with the modern history of Russia. Both literature and film gave an inspiration for a great public discussion on Stalin and stalinism. At the begining of that quarel the historians stood aside. During the course of discussion the official definition of stalinism was thrown away. According to that previous definition, stalinism was „an overcoming an illness of socialism” . That was stated by Nikita Chruszczów in his report during the XX Meeting of the Communist Party of the Soviet Union in 1956. Then the fundamental principles and the genesis of stalinism were declared. Also the connections with the revolution of 1917 year and policy of Bolsheviks were shown. There were even some attempts of interpretation the stalinism as a such kind of psychologic phenomena. These discussions are still over. They are an evidence of a great historic reorientation of the social memory of the past. The canon of official history was thrown away and that caused the appearance of many different, even contradictory histories. In many discourses the past is treated instrumentally. Many different explanations of it show us the deep political and religious divisions in the mentality of post soviet society.